BIOREMEDIATION - TECHNOLOGY FOR DECONTAMINATION OF SOILS POLLUTED WITH PETROLEUM HYDROCARBONS - Irina-Ramona PECINGINĂ; Daniela CÎRŢÎNĂ (Fiabilitate şi Durabilitate)
The pollution of soil with petroleum hydrocarbons prevents unfolding processes ofwater infiltration in soil, its circulation and the exchanges of the gaseous substances with theatmosphere. The biodegradation speed of the pollutants by the microorganisms is influenced ofsome factors: nutrients, soil type, humidity, temperature, pH, the type and the metabolism of themicroorganisms. The spill of the crude oil in the soil results in numerical growth of bacteriapopulations, with a concomitant reduction in their diversity, respectively with the predominantspecies that degrade hydrocarbons to simpler compounds, determining their gradualdisappearance.